Pelayanan Kesehatan Telinga Hidung Tenggorok Pada Masyarakat Daerah Pesisir di Kuta Pulau Lombok - Eka Arie Yuliyani; Hamsu Kadriyan; Didit Yudhanto; Triana Dyah Cahyawati; Ni Nyoman Geriputri; Dante Yustisia; Ika Prasetyaningrum (Universitas Mataram, 2022)
Traditional fishermen and divers are activities that are generally carried out by people in coastal areas. Kuta area, Mandalika is one of the coastal areas located on the island of Lombok. Diving activities and catching marine products are generally carried out in a hereditary manner and do not meet the Standard Operating Procedure (SOP) for safe and correct diving and are not followed by knowledge of the safety and health of diving so that it can cause problems in several organs of the body and the most often is the ear. In addition, health problems in coastal communities, especially in the field of ENT are also influenced by several factors including clean and healthy living behavior and environmental sanitation. Therefore, in this national social service activity, ENT health service activities and ear cleaning are carried out to obtain an overview of the health conditions of the people in coastal areas. The results of the ENT examination obtained in this activity are that in general the community has a good health status, although there are still several health problems that need attention, namely cerumen impaction and middle ear infection (CSOM), so it is necessary to carry out similar activities in coastal communities, especially on the island of Lombok to achieve better health status